Development and validation of a prognostic nomogram for myocardial infarction patients in intensive care units: a retrospective cohort study - Guo, Qi (BMJ Open, 2020)
OBJECTIVES: We aimed to develop and validate a prognostic nomogram and evaluate the discrimination of the nomogram model in order to improve the prediction of 30-day survival of critically ill myocardial infarction (MI) patients. DESIGN: A retrospective cohort study. SETTING: Data were collected from the Medical Information Mart for Intensive Care (MIMIC)-III database, consisting of critically ill participants between 2001 and 2012 in the USA. PARTICIPANTS: A total of 2031 adult critically ill patients with MI were enrolled from the MIMIC-III database. PRIMARY AND SECONDARY OUTCOME: Thirty-day survival. RESULTS: Independent prognostic factors, including age, heart rate, white blood cell count, blood urea nitrogen and bicarbonate, were identified by Cox regression model and used in the nomogram. Good agreement between the prediction and observation was indicated by the calibration curve for 30-day survival. The nomogram exhibited reasonably accurate discrimination (area under the receiver operating characteristic curve, 0.765, 95% CI, 0.716 to 0.814) and calibration (C-index, 0.758, 95% CI, 0.712 to 0.804) in the validation cohort. Decision curve analysis demonstrated that the nomogram was clinically beneficial. Additionally, participants could be classified into two risk groups by the nomogram, and the 30-day survival probability was significantly different between them (p<0.001). CONCLUSION: This five-factor nomogram can achieve a reasonable degree of accuracy to predict 30-day survival in critically ill MI patients and might be helpful for risk stratification and decision-making for MI patients.